Clinical characteristics and outcomes of ischemic stroke patients during Ramadan vs. non-Ramadan months: Is there a difference? - Alotaibi, Naser; Aldriweesh, Mohammed A.; Alhasson, Muath A.; Albdah, Bayan A.; Aldbas, Abdulaziz A.; Alluhidan, Waleed A.; Alsaif, Sultan A.; Almutairi, Faisal M.; Alskaini, Mohammed A.; Al Khathaami, Ali M. (Frontiers in Neurology, 2022)
Objectives To study the clinical characteristics and outcomes of patients experiencing an ischemic stroke during Ramadan vs. non-Ramadan months in a tertiary academic center in an Islamic country. Methods We retrospectively reviewed all patients with ischemic stroke (IS) in Ramadan and non-Ramadan months for four consecutive years (February 2016–June 2019). All demographics, vascular risk factors, laboratory results, modified Rankin Scale (mRS) at admission and discharge, National Institute Stroke Scale (NIHSS), and in-hospital complication data were collected for all patients. Results One thousand and 58 patients were included (non-Ramadan, n = 960; during Ramadan, n = 98). The mean age during Ramadan was 59 ± 13 years. Most non-Ramadan IS patients during Ramadan were male (68.5%; 57.1%, respectively). There was no statistical difference in vascular risk factors and medical history between the two groups. However, Ramadan patients had higher median NIHSS scores at discharge (p = 0.0045). In addition, more ICU admissions were noted among Ramadan patients (p = 0.009). In the gender-specific analysis for Ramadan patients, we found a statistically significant difference in smoking and urinary tract infection (p = 0.006, p = 0.005, respectively). Conclusion Based on our results, there was no difference, in general, between patients with IS during Ramadan and non-Ramadan months. However, IS patients had higher NIHSS scores at discharge and more ICU admissions during Ramadan. Last, we suggest future studies with larger sample sizes, longer duration, and including all types of strokes.